2019
DOI: 10.1002/jctb.5905
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of the Hg(II)‐volatilizing Bacillus sp. strain DC‐B2 and its potential to remediate Hg(II)‐contaminated soils

Abstract: BACKGROUND Mercury (Hg) contamination is a major global environmental problem, and its remediation using environmentally friendly biotechnologies has attracted increasing attention. In this study, an Hg(II)‐resistant bacterial strain, Bacillus sp. DC‐B2, was isolated from a metal‐contaminated site, and its ability to remediate five types of Hg‐contaminated soils was investigated. RESULTS The isolate DC‐B2 showed strong resistance to multiple metals and volatilized 91.6% of the Hg(II) in a culture with an initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 42 publications
(148 reference statements)
0
6
0
Order By: Relevance
“…In this isotherm model, suppressing chemical interactions were detected between the adsorbing molecules. In contrast, the Freundlich model shows that biosorption process was heterogeneous, non-uniform, and multi-layer and was not ideal ( Chen et al., 2019 ). In the Freundlich isotherm model, chemical interactions were seen between the adsorbed molecules ( Raoov et al., 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…In this isotherm model, suppressing chemical interactions were detected between the adsorbing molecules. In contrast, the Freundlich model shows that biosorption process was heterogeneous, non-uniform, and multi-layer and was not ideal ( Chen et al., 2019 ). In the Freundlich isotherm model, chemical interactions were seen between the adsorbed molecules ( Raoov et al., 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…1 Pseudo-firstorder ln q e − q t = lnq e − K 1 t Al-Hazmi, (2010) Not fitted K 1 is rate constant, q e and q t adsorbed metals at equilibrium times (h), and at a given time (t) 2 Pseudosecondorder suppressing chemical interactions were seen between the adsorbed molecules (Raoov et al, 2013). Similar results about fitted and nonuniform biosorption process (Chen et al, 2019). In this model, chemical interactions were seen between the adsorbed molecules (Raoov et al, 2013).…”
Section: R 2 Correlation Coefficient Valuesmentioning
confidence: 77%
“…The Langmuir model showed that the biosorption process was homogeneous, uniform, and monolayer, in which inhibitory chemical interactions were detected between the adsorbing molecules. Freundlich model biosorption process was heterogeneous, ununiform, multilayer, and not ideal (Chen et al., 2019 ), in which suppressing chemical interactions were seen between the adsorbed molecules (Raoov et al., 2013 ). Similar results about fitted Langmuir isotherm model were reported by Massoud et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mercury pollution in water could cause serious environmental and health problems because of the toxicity of mercury species to respiratory and nerve systems, [ 57 ] the detection and removal of mercury ion are hence important and have been widely investigated with the mercury absorbents including biomaterials, [ 58 ] covalent organic frameworks, [ 59 ] traditional diatomite, [ 60 ] chitosan, [ 61 ] or modified activated carbon. [ 62 ] Linear or hyperbranched polymers with abundant thioamide moieties as well‐known ligands for Hg 2+ , could hence be developed as Hg 2+ absorbents, [ 30,38 ] and hb ‐P 1 , hb ‐P 5 and hb ‐P 6 were studied as examples.…”
Section: Resultsmentioning
confidence: 99%